2004
DOI: 10.1242/dev.01047
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegansTRPV ion channel regulates 5HT biosynthesis in chemosensory neurons

Abstract: Serotonin (5HT) is a pivotal signaling molecule that modulates behavioral and endocrine responses to diverse chemical and physical stimuli. We report cell-specific regulation of 5HT biosynthesis by transient receptor potential V(TRPV) ion channels in C. elegans. Mutations in the TRPV genes osm-9 or ocr-2 dramatically downregulate the expression of the gene encoding the 5HT synthesis enzyme tryptophan hydroxylase(tph-1) in the serotonergic chemosensory neurons ADF, but neither the mutation nor the double mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
108
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 58 publications
7
108
0
1
Order By: Relevance
“…The reasons for this discrepancy are not understood. Related to this study, it was recently reported that TRPV2 could rescue one particular deficit of the ocr-2 mutant, namely the dramatic downregulation of serotonin biosynthesis in the sensory ADF neuron, but mammalian TRPV2, unlike TRPV4 directing behavior in osm-9, did not complement the lack of the osmotic avoidance reaction of ocr-2 (Zhang et al 2004, Sokolchik et al 2005. However, common to these two investigations is the conservation of TRPV signaling across phyla that have separated for several hundred million years of molecular evolution, despite low sequence homology.…”
Section: Mammalian Trpv4 Directs Osmotic Avoidance Behavior In C Elementioning
confidence: 66%
“…The reasons for this discrepancy are not understood. Related to this study, it was recently reported that TRPV2 could rescue one particular deficit of the ocr-2 mutant, namely the dramatic downregulation of serotonin biosynthesis in the sensory ADF neuron, but mammalian TRPV2, unlike TRPV4 directing behavior in osm-9, did not complement the lack of the osmotic avoidance reaction of ocr-2 (Zhang et al 2004, Sokolchik et al 2005. However, common to these two investigations is the conservation of TRPV signaling across phyla that have separated for several hundred million years of molecular evolution, despite low sequence homology.…”
Section: Mammalian Trpv4 Directs Osmotic Avoidance Behavior In C Elementioning
confidence: 66%
“…The functions of the TRPV channel encoded by the Caenorhabditis elegans ocr-2 and osm-9 genes in chemosensory neurons have been studied genetically (Colbert et al, 1997;de Bono et al, 2002;Tobin et al, 2002;Zhang et al, 2004). ocr-2 and osm-9 are coexpressed in four pairs of chemosensory neurons: the ADF serotonergic chemosensory neurons, the AWA olfactory neurons, the ASH osmotic sensory neurons, and the ADL chemosensory neurons .…”
Section: Introductionmentioning
confidence: 99%
“…Both OSM-9 and OCR-2 are localized to the cilia, as well as to the plasma membrane . Null mutations in either ocr-2 or osm-9 cause downregulation of the expression of the tph-1 gene, which encodes the key serotonin (5-HT) biosynthetic enzyme tryptophan hydroxylase, in the ADF neurons (Zhang et al, 2004), and the odr-10 gene, which encodes a receptor for the odorant diacetyl (Sengupta et al, 1996), in the AWA neurons . Both OCR-2 and OSM-9 also are required for ASH-mediated osmotic sensation and ASH-and ADL-mediated olfactory avoidance (Colbert et al, 1997;Tobin et al, 2002); however, several efforts have not been able to identify an effect of the activity of this channel on the expression of sensory components in ASH and ADL (I. Sokolchik and J. Sze, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations